A Hermeneutic Phenomenological Inquiry at a Canadian University: Protective and Risk Factors for Chinese International Students in COVID Times with Gender Comparison - Ge, Lin (Journal of International Students, 2021)
This hermeneutic phenomenological inquiry explores the lived experiences of Chinese international students at a Canadian university in COVID times with gender comparison. Ten participants between 20 and 30 years of age are interviewed via Zoom meetings and WeChat videos to reveal specific insights they have gained from their experiences. Based on resilience theory as a theoretical framework, the findings display the students’ protective factors, including internal assets and external resources, i.e., perceived competence, coping skills, self-efficacy, family connectedness, parental support, peer support, school connectedness, and community support, and the risk factors the students face during these challenging times, i.e., academic barriers, mental issues, health threats, and racial prejudges. The interactions of protective factors and risk factors are examined, in reducing or avoiding the negative effects of adversity exposure. Special resilience-based interventions are discussed.